PTU-102 Critical Care Nutrition in the United Kingdom – A Survey of Current Practice. (17th August 2016) - FitzPatrick, M; Stroud, MA; De Silva, A
Abstract : Introduction: Patients in the intensive care unit (ICU) are at high risk of malnutrition. Consensus guidelines recommend a dietitian be part of the ICU team and available within working hours, and hospitals have a nutrition support team (NST) for patients with complex needs. We investigated the provision of nutrition support and patterns of dietetic practice on ICUs in the UK. Methods: An online survey was sent to members of the Parenteral and Enteral Nutrition Group and Critical Care Group of the British Dietetic Association (n = 560). Results were analysed in Microsoft® Excel. Results: There were 166 responses, 141 from dietitians, an estimated response rate of 30%. 134 (81%) worked in England, 18 in Scotland and 11 in Wales. Most (136, 82%) were from general ICUs, with 30 (18%) from specialist ICUs including 8 cardiac units, 8 neurosciences units, 6 transplant units, 6 HPB/liver units, 4 trauma centres, 3 burns units, 3 intestinal failure units and 1 oncology unit. Only 88 respondents (53%) said their unit had a dedicated ICU dietitian, although 149 (90%) had regular dietitian support. Only 78 respondents (47%) said their unit had dietitian input every weekday. 137 respondents (83%) said their unit had access to an NST but only 103 (62%) stated the NST attended the ICU regularly. 153 respondents (92%) said all patients on parenteral nutrition would receive dietitian input on their unit and 132 (80%) said all those on enteral nutrition would have dietitian input. Only 60 respondents (36%) said all ICU patients would have dietitian input. 107 units (64%) used actual body weight to calculate patient requirements, whilst 48 units (29%) used estimated body weight. 11 units (7%) used ideal body weight. 79% (124/156) of respondents used an equation model to calculate requirements, most commonly the Henry (53%) and Penn State equations (37%). There was significant variation in kcal/kg (range 10–35 kcal/kg, median 20–25 kcal/kg) and nitrogen intake (range 0.05–0.25 gN/kg, median 0.15–0.20 gN/kg) targets between units. 153 (94%) respondents stated their unit used gastric residual volume (GRV) to guide enteral feeding, with GRVs triggering a reduction in feed rate ranging from 200 ml to 500 ml. Specialist supplemental feeds were not commonly used, although 16 (10%) respondents said their unit used glutamine. 126 (79%) respondents said their unit followed NICE guidelines on refeeding syndrome. Conclusion: Whilst dietitian and NST input is available on most ICUs, half of units lack a dedicated ICU dietitian, do not have daily dietitian involvement and lack regular NST input. There is significant variation in the methods used to calculate patient requirements, in the use of GRV and of specialist supplementation. National guidance for critical care nutrition may help reduce disparities in dietetic provision. Disclosure of Interest: None Declared